The critical factors for successfully applying lean tools in the Egyptian construction sector - Shaqour, Eman; Alshafei, Islam A.; AbuKarki, Hanan; Almashhour, Rashwan T. N. (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
Lean construction has gained global recognition for improving efficiency, yet its adoption in Egypt remains hindered by numerous barriers. This study empirically investigates the key factors influencing the successful implementation and adoption of lean construction practices in Egypt. Using a data-driven methodology, the research identifies the five most critical CSFs are: awareness of lean philosophy, elimination of design errors, effective management of the production chain, strong collaborative relationships, and a robust work plan with comprehensive risk planning. An extensive review of previous research was conducted to identify Critical Success Factors (CSFs), resulting in a list of 27 factors included in a survey. A questionnaire was distributed to 162 practitioners involved in construction projects to evaluate the significance of these CSFs in the Egyptian context. Various statistical analyses were performed using IBM SPSS Statistics, including validity and reliability tests, descriptive statistics for ranking the CSFs, and principal component analysis (PCA) to identify the primary drivers of lean construction success. Beyond demonstrating established CSFs, the findings underscore their contextual relevance in a developing economy, offering practical guidance for industry stakeholders and extending theoretical insights into lean implementation across construction environments.